Smartphone Device Monitoring System Using Google Family Link (D’Paragon Housekeeping and Cleaning Service Case Study) - Mustofa, Muhammad; Ady Prabowo, Iwan; Wijayanto, Hendro (Department of Informatics Universitas Islam Indonesia, 2024)
D'Paragon Kost is an exclusive boarding house based in Yogyakarta and has approximately 38 branches. Spread throughout Indonesia and in each branch there are employees who serve as Housekeeping and Cleaning Services. At each Housekeeping and Cleaning Service, facilities are provided in the form of a Smartphone device which is useful for reporting scheduled activities. Using a smartphone that is not intended can cause problems with the smartphone. After the IT team investigated the branch location, there were applications that were outside the company's operational standards. So precautions are taken so that smartphone facilities cannot be used to access applications outside of standard procedures. There are several types of applications that can control smartphone devices. One of these applications is Google Family Link. The aim is to remotely control the Housekeeping and Cleaning Service smartphone and limit the performance of the smartphone itself. As a data collection sample, the author used 5 (five) days of data from 4 (four) Housekeeping and 1 (one) Cleaning Service with different assignment locations and jobs. The data used is daily application usage data in minutes and standard application data from D'Paragon Kost. From the analysis of application usage behavior in each branch, the number of working hours does not affect the lack of access to certain applications. If this behavior is outside the company's Standard Operating Procedures (SOP), it can reduce employee performance. This is shown by the existence of the Cleaning Service branch which has been using the YouTube application for longer than other branches. So monitoring each branch in the use of smartphones with Google Family is very effective in knowing employee behavior at work. The company can also provide recommendations regarding the use and access of smartphones according to their intended use.